Dealing with discordant genetic signal caused by hybridisation, incomplete lineage sorting and paucity of primary nucleotide homologies: a case study of closely related members of the genus Picris subsection Hieracioides (Compositae). - Marek Slovák; Jaromír Kučera; Eliška Záveská; Peter Vd'ačný (PLoS ONE, 2014)
We investigated genetic variation and evolutionary history of closely related taxa of Picris subsect. Hieracioides with major focus on the widely distributed P. hieracioides and its closely related congeners, P. hispidissima, P. japonica, P. olympica, and P. nuristanica. Accessions from 140 sample sites of the investigated Picris taxa were analyzed on the infra- and the inter-specific level using nuclear (ITS1-5.8S-ITS2 region) and chloroplast (rpl32-trnL(UAG) region) DNA sequences. Genetic patterns of P. hieracioides, P. hispidissima, and P. olympica were shown to be incongruent and, in several cases, both plastid and nuclear alleles transcended borders of the taxa and genetic lineages. The widespread P. hieracioides was genetically highly variable and non-monophyletic across both markers, with allele groups having particular geographic distributions. Generally, all gene trees and networks displayed only a limited and statistically rather unsupported resolution among ingroup taxa causing their phylogenetic relationships to remain rather unresolved. More light on these intricate evolutionary relationships was cast by the Bayesian coalescent-based analysis, although some relationships were still left unresolved. A combination of suite of phylogenetic analyses revealed the ingroup taxa to represent a complex of genetically closely related and morphologically similar entities that have undergone a highly dynamic and recent evolution. This has been especially affected by the extensive and recurrent gene flow among and within the studied taxa and/or by the maintenance of ancestral variation. Paucity of phylogenetically informative signal further hampers the reconstruction of relationships on the infra- as well as on the inter-specific level. In the present study, we have demonstrated that a combination of various phylogenetic analyses of datasets with extremely complex and incongruent phylogenetic signal may shed more light on the interrelationships and evolutionary history of analysed species groups.